Řízení jakosti společnosti Tyco Electronics EC Trutnov, s.r.o. - Urbanová, Lucie (Univerzita Pardubice, 2006)
Tato bakalářská práce se zabývá systémem řízení jakosti a jeho uplatněním ve společnosti TEET. V teoretické části je vysvětlen pojem jakost, management jakosti, politika a cíle jakosti. Praktická část je zaměřena na systém řízení jakosti ve společnosti TEET. Práce popisuje význam spolupráce s dodavateli a uplatnění norem ISO.

This bachelor work deals with system of quality management and its applications in TEET company. In the teoretical part is explained the quality concept, the management of quality, the politic and the objectives of quality. The practical part is focused in system quality management in TEET company. The work describes the importance of cooperation with suppliers and use norms ISO.
Quality management in Tyco Electronics EC Trutnov, s . r. o. company
Keywords: Quality; Quality Management; norms ISO; certification; Jakost; řízení jakosti; normy ISO; certifikace